Integrating psychosocial skill and characteristic development into an English academy soccer coaching program: a preliminary investigation - Mitchell, T. O., Cowburn, I. H., Alder, D. B., Till, K., Littlewood, M. A., Cook, T., & Piggott, D. (International Sport Coaching Journal, 2025)
This study aimed to assess the impact of a psychosocial development program on academy soccer players with coaches being central design and delivery. The 8 Pillars program (designed to foster Communication, Control, Commitment, Confidence, Concentration, Resilience, Presence, and Self-awareness) was delivered through player workshops, coaching practice, and coach-led environmental manipulation. A total of 25 academy soccer players (Mage 14.7 ± 0.3) completed the Psychological Characteristics of Development Excellence Questionnaire-2 pre- and postseason, and a self-report scale for each of the eight prescribed psychosocial skills and characteristics at five time points across the season. Significant (p < .05) improvement between pre- and postseason for "Imagery and Active Preparation," "Seeking and Using Social Support," and "Active Coping" factors within the Psychological Characteristics of Development Excellence Questionnaire-2 were evident. Significant (p < .05) improvements were shown for "Communication," "Control," "Commitment," "Concentration," and "Resilience" scales across the season. These findings give initial efficacy that a targeted, multifaceted program, largely delivered by coaches, can improve player self-reported psychosocial skills and characteristics in a U.K. academy soccer setting.